Thylakoid Lumen; from “proton bag” to photosynthetic functionally important compartment - Farci, Domenica; Schröder, Wolfgang P. (Frontiers in Plant Physiology, 2023)
This mini review provides an update of the thylakoid lumen, shedding light on its intricate structure, unique proteome, and potential physiological significance. This compartment within the thylakoid membranes of chloroplasts was originally perceived as “empty”, only providing a site for proton accumulation to support ATP formation. Instead, recent investigations have revealed that the lumen houses a specific set of proteins each with potentially critical roles. The structure of this compartment has been shown to be dynamic, with changes in size and organization influenced by light exposure, impacting protein mobility and function. Noteworthy, some of the lumen proteins are permanently or transiently in contact with protein complexes located in the thylakoid membrane, such as PSII (PsbP-like and PsbQ-like proteins) cytochrome b6f, and PSI. Meanwhile, other lumen proteins seems to be more “independent” such as proteases, immunophilins, stress-related proteins, pentapeptide repeat proteins, and many others with unknown functions. All these proteins play crucial roles in maintaining photosynthetic machinery, adapting to environmental stress, and regulating cellular processes. Understanding the lumen’s function is vital as it holds promise for uncovering novel regulatory interactions and signaling pathways within the chloroplast.